The state of emergency department extracorporeal cardiopulmonary resuscitation: Where are we now, and where are we going? - Anna L. Ciullo; Joseph E. Tonna (Journal of the American College of Emergency Physicians Open, 2024)
Abstract Extracorporeal cardiopulmonary resuscitation (ECPR) has emerged in the context of the emergency department as a life‐saving therapy for patients with refractory cardiac arrest. This review examines the utility of ECPR based on current evidence gleaned from three pivotal trials: the ARREST trial, the Prague study, and the INCEPTION trial. We also discuss several considerations in the care of these complex patients, including prehospital strategy, patient selection, and postcardiac arrest management. Collectively, the evidence from these trials emphasizes the growing significance of ECPR as a viable intervention, highlighting its potential for improved outcomes and survival rates in patients with refractory cardiac arrest when employed judiciously. As such, these findings advocate the need for further research and protocol development to optimize its use in diverse clinical scenarios.